Low Energy Diets for Obesity and CKD (SLOW-CKD Randomized Feasibility Study) - Marguerite M. Conley; Hannah L. Mayr; Kirsten S. Hepburn; Justin J. Holland; David W. Mudge; Tammy J. Tonges; Richard S. Modderman; Sally A. Gerzina; David W. Johnson; Andrea K. Viecelli; Helen L. MacLaughlin (Kidney International Reports)
Introduction: Low energy diets (LEDs) may slow disease progression; however, their effects are under researched in chronic kidney disease (CKD). This study evaluated the safety and feasibility of an LED weight management program in adults with obesity and CKD. Methods: This multicenter 6-month randomized controlled trial (RCT) involved adults with CKD Kidney Disease: Improving Global Outcomes stages G1 to G3b, obesity, and proteinuria, randomized 1:1 into 2 groups. The LED group followed a 3-month 800 to 900 kcal/d LED, with dietitian support, then a 3-month weight maintenance phase with exercise and healthy eating support. The usual care (UC) group received standard clinic weight loss support. Primary outcomes were safety (serious adverse events [SAEs]) and feasibility (≥2 of recruitment rate ≥ 25%, LED group retention rate ≥ 75%, and ≥ 30% of LED group achieving ≥ 10 kg weight loss at 3 months). Secondary outcomes included changes in anthropometry, clinical measures, patient-reported outcomes, and participant experiences. Results: Forty-nine participants (median age 51 years, 57% male) consented. SAEs were low and comparable as follows: 2 in the LED group (hypoglycemia and acute kidney injury) and 2 in the UC group (hypoglycemia), all requiring hospitalization. Feasibility was met for recruitment (46%) and weight loss (46% achieved ≥ 10 kg loss) but not for retention (67% retained). At 6 months, median (IQR) weight change was −9.0 kg (−12 to −7) in the LED group and 0 kg (−4 to 2) in the UC group (P < 0.001). Conclusion: LEDs under professional guidance are safe and feasible for weight loss in adults with obesity and CKD Kidney Disease: Improving Global Outcomes stages G1 to G3b. A definitive RCT to assess their effects on clinical outcomes and CKD progression is warranted.